Taqâlîd al-Zawâj fî al-I’tiqâd al-Jâwiy (al-Dirâsah al-Naqdiyyah). - Adib Fuadi Nuriz; Azzamul Azhar (Journal of Comparative Study of Religions (JCSR), 2020)
This research focuses on solutions to the Javanese Muslim community in order to be able to carry out marriages with Javanese customs which are suitable with Islamic values and avoided from shirk. This research is a qualitative research with a cultural antrolopology approach. The data is taken from the library as library research, such as books and articles that explain the procedures for marriage with Javanese customs. By using descriptive-analytical method, the researcher analyzes the procedures of marriage with Javanese customs which are in accordance with Islam and which are contrary to Islamic sharia based on theory ‘urfin Islam. The results showed that there were six kinds of rituals and symbols that contained elements of shirk and violated the Islamic shari'a, those are 1) the ritual of determining the good day to carry out the marriage; 2) the ritual of choosing a mate by counting weton; 3) wear claw patterned fabric when installing tarub; 4) the splash ritual; 5) midodareni, and 6) betel throw.